2015
DOI: 10.17675/2305-6894-2015-4-4-6
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and corrosion inhibiting behavior of Passiflora foetida leaf extract on mild steel corrosion

Abstract: Passiflora foetida leaf extract (PFLE) as a corrosion inhibitor in 1 M HCl was investigated by weight loss method and electrochemical techniques. Inhibition efficiency of PFLE was found to increase with increasing concentration. Polarization measurements revealed that the PFLE acted as a mixed type inhibitor. Nyquist plots showed that on increasing the PFLE concentration, the charge transfer resistance increased and double layer capacitance decreased. The adsorption of PFLE on mild steel obeyed the Langmuir ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The results of the study are summarized in Table 2. Analysis of the Table 2 shows that increasing the concentration of the inhibitor was accompanied by a decrease in the rate of corrosion and led to increasing of the inhibition efficiency, this due to the fact that the adsorption coverage increases, which shields the carbon steel surface efficiently from the medium [17]. This decrease was significant even at low concentrations.…”
Section: Weight Loss Testsmentioning
confidence: 99%
“…The results of the study are summarized in Table 2. Analysis of the Table 2 shows that increasing the concentration of the inhibitor was accompanied by a decrease in the rate of corrosion and led to increasing of the inhibition efficiency, this due to the fact that the adsorption coverage increases, which shields the carbon steel surface efficiently from the medium [17]. This decrease was significant even at low concentrations.…”
Section: Weight Loss Testsmentioning
confidence: 99%
“…[14,19,[21][22][23]. Furthermore, research has revealed that the basic components of plant extracts are alkaloids, steroids, sugars, gallic acid, tannic acid, and flavonoids, which have been found to improve the protection of metal surface against corrosion [24][25][26].…”
Section: F E + H + → F E 2+ + Hmentioning
confidence: 99%
“…Corrosion inhibition of mild steel in 1 M HCl in presence of MPSE can be explained on the basis of molecular adsorption [16]. MPSE inhibits the corrosion of mild steel by controlling both the anodic and cathodic reactions.…”
Section: Mechanism Of Inhibitionmentioning
confidence: 99%
“…Moreover, Plant extracts contain a variety of natural products such as essential oils, tannins, pigments, steroids, terpenes, flavones and flavonoids, among other well-known active substances used as corrosion inhibitors [14][15][16]. These compounds often present conjugated aromatic structures, long aliphatic chains bearing N, S, and O heteroatoms with free electron pairs available to bond with the metal surface.…”
Section: Introductionmentioning
confidence: 99%